Pembelajaran Double Loop Problem Solving di Kelas VII-A MTs Negeri 3 Banyumas untuk Meningkatkan Kemampuan Komunikasi Matematis dan Self-Efficacy - Zulaeha Nur Asyifa; Anton Jaelani (AlphaMath : Journal of Mathematics Education, 2019)
This study aimed to enhance mathematical communication ability and self-efficacy on seventh-grade students through Double Loop Problem Solving learning at MTs Negeri 3 Banyumas. The subjects was 26 seventh-grade students from MTs Negeri 3 Banyumas in academic year of 2018/2019. This research was a class action research consisting of 3 cycles. The instrument was the test to measure mathematical communication ability and the questionnaire to measure self-efficacy. The results are the average score of mathematical communication ability in cycle I, cycle II, and cycle III respectively are 52,03; 74,02; dan 76,58. In addition, the average score of self-efficacy in cycle I, cycle II, and cycle III respectively are 68,59; 72,80; and 75,64.